The Influence of Using Cybersex Applications on Student Behavior SMA N 1 Dempet: Pengaruh Penggunaan Aplikasi Cybersex Terhadap Perilaku Siswa SMA N 1 Dempet - Ulfa Nur Khofifah; Retnaningdyastuti Retnaningdyastuti; MA Primaningrum Dian (International Journal of Technology Vocational Education and Training, 2021)
This research was motivated by the existence of students accessing cybersex applications, which happened to students at SMA N 1 Dempet. This is based on curiosity when viewing impressions on the cybersex application. The problem that will be revealed in this study is how the behavior of students because of the cybersex application. The purpose to be achieved in this study is to determine the behavior carried out in relation to the cybersex application. This type of research is qualitative with the case study method. Respondents in this study were students of SMA N 1 Dempet as many as 3 respondents, 3 parents of respondents, 3 close friends of the respondents, and 1 teacher of the Respondent Counseling. The data in this study were obtained through interviews, observation and documentation. The effect of the use of cybersex applications on student behavior, namely students with increasingly sophisticated technological lives, are easier for behavior in accessing cybersex activities such as viewing pornographic photos / videos, accessing pornographic literature, and having sex chats with a wider range of other people. As well as getting pleasure when accessing it and also getting a conflict in him about the influence of using the cybersex application